2020
DOI: 10.1093/jxb/eraa330
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 has concurrent effects on leaf and grain metabolism but minimal effects on yield in wheat

Abstract: While the general effect of CO2 enrichment on photosynthesis, stomatal conductance, nitrogen elemental content or yield has been documented, there is still some uncertainty as to whether there are interactive effects between CO2 enrichment and other factors (such as temperature, geographical location, water availability and cultivar). In addition, the metabolic coordination between leaves and grains, which is crucial for crop responsiveness to elevated CO2, has never been examined closely. Here, we addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 88 publications
5
18
0
Order By: Relevance
“…A recent study involving five FACE facilities in Germany, Italy, China, Australia, and the USA under relatively dry conditions with total rainfall during the growing season ranging between 141 and 347 mm year –1 showed that exposure to elevated [CO 2 ] of + 150 μmol mol −1 did not affect yield and photosynthetic rate of wheat in almost all sites (with the only exception of the USA site) 41 . In general, the lack of a CO 2 effect on yield was explained by an unchanged assimilation rate, concluding that the effect of CO 2 on yield is highly dependent on local environmental conditions (e.g., water availability, N fertilization rate, soil type), acclimation capacity, and cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study involving five FACE facilities in Germany, Italy, China, Australia, and the USA under relatively dry conditions with total rainfall during the growing season ranging between 141 and 347 mm year –1 showed that exposure to elevated [CO 2 ] of + 150 μmol mol −1 did not affect yield and photosynthetic rate of wheat in almost all sites (with the only exception of the USA site) 41 . In general, the lack of a CO 2 effect on yield was explained by an unchanged assimilation rate, concluding that the effect of CO 2 on yield is highly dependent on local environmental conditions (e.g., water availability, N fertilization rate, soil type), acclimation capacity, and cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf chlorophyll content was reduced at elevated CO 2 because of pigment degradation from lower nitrogen metabolism (Haque et al, 2006; Tcherkez et al, 2020). Genetic variation in leaf chlorophyll was reported to significantly impact wheat heat tolerance (Javed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Quality deterioration due to lower protein via reduced N is of critical concern in future high CO 2 climate considering that even additional supply of N does not prevent N dilution in grain under eCO 2 (Tausz et al 2017). In addition, eCO 2 has strong detrimental effect on other nutrient availability and remobilization from leaves to grains (Tcherkez et al 2020).…”
Section: Elevated Co 2 Reduced Grain N In Yitpi Onlymentioning
confidence: 99%